2020
DOI: 10.1002/anie.202003421
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Sieving of C2‐C3 Alkene from Alkyne with Tuned Threshold Pressure in Robust Layered Metal–Organic Frameworks

Abstract: C2‐C3 alkyne/alkene separation is of great importance; however, designing materials for an efficient molecular sieving of alkenes from alkynes remains challenging. Now, two hydrolytically stable layered MOFs, [Cu(dps)2(GeF6)] (GeFSIX‐dps‐Cu, dps=4,4′‐dipyridylsulfide) and [Zn(dps)2(GeF6)] (GeFSIX‐dps‐Zn), can achieve almost complete exclusion of both C3H6 and C2H4 from their alkyne analogues. GeFSIX‐dps‐Cu displays a notable advanced threshold pressure for alkynes adsorption and thus substantial uptakes at low… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
89
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(94 citation statements)
references
References 45 publications
4
89
0
1
Order By: Relevance
“…[4] Forsmaller gas molecule,t he gate-opening pressure is also lower as smaller degree of structural change is needed to accommodate smaller molecule in the pore. [5] Selective gate-opening adsorption has realized several important binary gas separation [6] with high sieving performance that is comparable to those of rigid sieving MOFs.…”
Section: Introductionmentioning
confidence: 99%
“…[4] Forsmaller gas molecule,t he gate-opening pressure is also lower as smaller degree of structural change is needed to accommodate smaller molecule in the pore. [5] Selective gate-opening adsorption has realized several important binary gas separation [6] with high sieving performance that is comparable to those of rigid sieving MOFs.…”
Section: Introductionmentioning
confidence: 99%
“…The N 2 isotherm exhibits typical type I adsorption behavior characteristic of microporous materials (Figure 3 a). The BET surface area was calculated to be 1330 m 2 g −1 , which is distinctly higher than those of most ultra‐microporous fluorinated MOFs, including famous SIFSIX‐1‐Cu (1178 m 2 g −1 ), [8e] SIFSIX‐2‐Cu‐i (685 m 2 g −1 ), [8e] UTSA‐200a (612 m 2 g −1 ), [8c] UTSA‐300a (311 m 2 g −1 ) [8d] and GeFSIX‐dps‐Cu (382 m 2 g −1 ) [13] . The pore volume was calculated to be 0.52 cm 3 g −1 , which matches well with the theoretical value of 0.51 cm 3 g −1 .…”
Section: Methodsmentioning
confidence: 94%
“…116,117 In 2017, Li et al 96 reported C , exemplified by ZJUT-1, SIFSIX-14-Cu-i (UTSA-200), TIFSIX-14-Cu-i (ZU-13), and GeFSIX-dps-Cu/Zn. 58,[119][120][121]…”
Section: H 4 /C 3 H 6 Separationmentioning
confidence: 99%
“…The selectivity towards C 3 H 4 was attributed to C−H···F hydrogen bonds between propyne molecules and the F atoms of the linker ligands. Other reports of selective adsorption of C 3 H 4 over C 3 H 6 have focused on hybrid porous materials with inorganic anionic pillars of SiF 6 2− , TiF 6 2− , and GeF 6 2− , exemplified by ZJUT‐1, SIFSIX‐14‐Cu‐i (UTSA‐200), TIFSIX‐14‐Cu‐i (ZU‐13), and GeFSIX‐dps‐Cu/Zn 58,119–121 …”
Section: Chronology Of the Development Of Pcns For C3 Hc Separationmentioning
confidence: 99%